How Digital Communication is Reshaping Interpersonal Relationships in Urban India: A Study of Communication Trends Among Young Adults - Raktavati Holkar (Journal of Public Representative and Society Provision, 2022)
The effects of online media on friendships among young people in metropolitan India are investigated. Convenience sampling was used to enroll 100 participants, and data was gathered from semi-structured interviews. Convenience, long-distance relationships, communication network, overwhelm, anxiety, and less face-to-face contact were the six themes that emerged from the data analysis. The findings imply that while digital communication facilitates convenience and aids in maintaining long-distance relationships, it can also contribute to feelings of overload and anxiety due to the constant flow of information. In addition, less time is spent talking to people face-to-face because of digital contact. The results of this study shed light on the impact that technology has on the social lives of metropolitan Indian youth.